A multi-layer high temperature resistant heat insulation composite material and preparation method thereof
By adopting multi-layer structure high-temperature heat-resistant composite materials, combined with single-sided heating sintering and ceramic fiber wire connection technology, the existing thermal protection materials have been solved, and the problems of high cost, long cycle and low bonding strength have been achieved, achieving high efficiency and economical Thermal protection effect.
Patent Information
- Application Number
- CN202411658598.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-20
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2044-11-20
AI Technical Summary
The external thermal protection materials of existing ultra-high-speed aircraft have problems such as high production cost, long production cycle, poor material density and low bonding strength.
Using multi-layer structure high-temperature heat-resistant composite materials, including high-density ceramic composite materials layer, fiber felt reinforced ceramic composite materials layer, aerogel thermal insulation composite materials layer and resin-based composite materials layer, sintering and ceramic fibers through single-sided heating Wire connection and other technologies can achieve rapid forming and efficient bonding of materials.
It achieves an excellent combination of the high-temperature ablation resistance of the upper panel and the high-strength bonding performance of the lower panel, reducing material costs and production cycles, and is suitable for large-scale mass production.
Smart Images

Figure CN119159876B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a high temperature resistant heat insulating composite material, in particular to a multi-layer high temperature resistant heat insulating composite material and a preparation method thereof, belonging to the technical field of thermal protection materials for aerospace. Background Art
[0002] In order to solve the problem of thermal protection of the exterior of existing hypersonic aircraft, in recent years, it has become a trend to prepare sandwich composite materials with aerogel composite materials as the thermal insulation core layer and anti-burning panel materials on the outer surface, such as Chinese patent publication numbers: CN102642350A, CN108116002A, CN109824372A and CN111703142A, etc. Although the above disclosed technologies are targeted, their materials are basically a sandwich structure, with an upper and lower layer of fiber-reinforced ceramic-based composite panels sandwiching a layer of aerogel composite material, wherein the upper panel mainly functions as high temperature resistance and ablation resistance, and the lower panel is mainly used for bonding with the metal bearing structure. The main scheme basically includes: 1) supercritical drying and other processes combined with a mold forming scheme to make aerogel composite materials as the thermal insulation core layer; 2) overall stitching of the upper and lower surface fiber fabrics; 3) sol-gel process combined with a mold forming scheme to densify and shape the upper and lower surface fabrics, and ceramic sintering to form upper and lower panels of ceramic composite materials with the same matrix. The above schemes may need to be improved in the following aspects during the actual forming and manufacturing of thermal protection structural parts: 1) The production of the thermal insulation core layer needs to be highly customized, and the corresponding forming molds may need to be matched and mechanical processing may be required, which has high production costs; 2) The sol-gel process requires repeated dipping, curing and drying for several or even dozens of times, and the production cycle is very long, and the consumption of sol and other materials is very large; 3) Regardless of whether the sol immersion process is at normal pressure or vacuum, the thermal insulation core material will absorb a certain amount of sol matrix, thereby increasing its density and reducing its thermal insulation and other properties; 4) There is a large density difference between the upper panel and the thermal insulation core layer of the manufactured sandwich structure, and the interface reliability is not high under the combined environment of high temperature and deformation stress; 5) The overall dipping process of the sol-gel process makes the upper and lower panels only porous ceramic composite materials of the same matrix. Since the lower panel is easy to form a matrix with low bonding strength on the surface, the strength of the adhesive when bonded to the metal structure is very low (the matrix falls off, and the bonding strength is much lower than the strength of the adhesive itself). Summary of the invention
[0003] In order to solve the technical problems existing in the prior art, the first purpose of the present invention is to provide a multi-layer structure high temperature resistant heat insulation composite material, which realizes the excellent combination of the high temperature resistance and ablation resistance of the upper panel and the bonding performance of the lower panel. More specifically, it has a multi-layer structure: the upper panel is a high-density ceramic composite material layer, which has excellent heat protection, ablation resistance, erosion resistance, load-bearing and other functions; the transition layer is a fiber felt reinforced ceramic composite material layer, which has the functions of adjusting thickness and thermal deformation matching; the middle layer is an aerogel heat insulation composite material layer, which plays the role of heat insulation and load transfer; and the lower panel is a resin-based composite material layer, which plays the role of high-strength bonding with the metal load-bearing structure.
[0004] The second object of the present invention is to provide a method for preparing a multilayer high temperature resistant heat insulating composite material, which has the advantages of short production cycle and low cost, and is easy to realize large-scale batch production.
[0005] In order to achieve the above technical objectives, the present invention provides a multilayer high-temperature resistant thermal insulation composite material, which includes, from top to bottom, a high-density ceramic composite material layer, a fiber felt reinforced ceramic composite material layer, an aerogel thermal insulation composite material layer and a resin-based composite material layer; wherein the high-density ceramic composite material layer is composed of an oxide fiber cloth reinforcement phase and an oxide ceramic phase, the fiber felt reinforced ceramic composite material layer is composed of an oxide fiber felt reinforcement phase and an oxide ceramic phase, the aerogel thermal insulation composite material layer is composed of an oxide fiber felt reinforcement phase and an oxide aerogel, and the resin-based composite material layer is composed of an oxide fiber cloth reinforcement phase and a resin matrix.
[0006] The multi-layer structure of the high-temperature resistant thermal insulation composite material of the present invention has an upper panel layer which is a high-density ceramic composite material layer, which has the characteristics of high density and high strength, and its functions mainly include heat protection, ablation resistance, erosion resistance, load bearing, etc.; the transition layer is a fiber felt reinforced ceramic composite material layer, and its density and strength are between those of the upper panel and the middle layer (aerogel thermal insulation composite material), which plays a role in adjusting thickness and thermal deformation matching, etc.; the middle layer is a multi-layer aerogel thermal insulation composite material layer, and its functions mainly include heat insulation and load transfer functions; the lower panel layer is a resin-based composite material layer, which plays a role in high-strength bonding with the metal load-bearing structure.
[0007] As a preferred solution, in the high-density ceramic composite material layer, the oxide ceramic phase includes at least one of alumina, mullite, silicon oxide or zirconium oxide; the oxide fiber cloth reinforcement phase is composed of multiple layers of oxide fiber cloth, each layer of oxide fiber cloth has a thickness of 0.1-0.5 mm, and the total thickness is 0.5-10 mm. The thickness of each layer of oxide fiber cloth is further preferably 0.1-0.2 mm. Compared with the relatively thick oxide fiber cloth, the use of a thin layer of oxide fiber cloth is more conducive to the uniform saturation infiltration of the oxide slurry. The total thickness of the oxide fiber cloth is further preferably 1-2 mm, which can basically meet the requirements of high-temperature ablation resistance required by the usual thermal environment, and the thin panel can make the overall structure have a lower density. As a more preferred solution, the oxide fiber cloth includes at least one of quartz fiber cloth, alumina fiber cloth, mullite fiber cloth, and zirconium oxide fiber cloth. It should be noted that the oxide ceramic phase is preferably matched with oxide fiber cloth with the same chemical composition.
[0008] As a preferred solution, in the fiber felt reinforced ceramic composite material layer, the oxide ceramic phase includes at least one of alumina, mullite, silicon oxide or zirconium oxide, and the oxide fiber felt reinforcement phase is composed of oxide fiber felt. The fiber felt used in the transition layer has a lower density than the fiber cloth, which can reduce the density of the transition layer composite material, and the felt body is fluffy and has better elasticity, which is conducive to adjusting the overall thickness during the pressing process. As a more preferred solution, the density of the oxide fiber felt is 0.1~0.5 g / cm 3 As a more preferred solution, the oxide fiber felt includes at least one of quartz fiber felt, alumina fiber felt, mullite fiber felt, and zirconia fiber felt.
[0009] As a preferred solution, in the aerogel thermal insulation composite material layer, the aerogel includes at least one of silica aerogel, alumina aerogel, silica-alumina binary aerogel, and mullite aerogel, and the oxide fiber felt reinforcement phase is composed of high temperature resistant fibers. As a more preferred solution, the high temperature resistant fibers include at least one of quartz fibers, alumina fibers, basalt short fibers, and mullite fibers. As a more preferred solution, the aerogel thermal insulation composite material layer is composed of multiple single-layer aerogel thermal insulation composite material layers, with a total thickness between 3 and 50 mm, and a thickness of each single layer between 0.3 and 3 mm. The total thickness of the aerogel thermal insulation composite material layer is further preferably between 5 and 30 mm, which can meet the required insulation requirements under normal thermal environment conditions. The thickness of each single-layer aerogel thermal insulation composite material layer is further preferably 1 to 2 mm, which can meet the better deformation performance during the pressing process from a flat plate to an arc structure. On the one hand, theoretically, the thinner each layer of thermal insulation material is (as thin as a book page), the more conducive it is to compression deformation, but too many layers will increase the interlayer interface and the workload of layering; on the other hand, if there are too few layers, the thickness of a single layer will be too large, and it is easy to crack, wrinkle and other problems when bent into an arc. The aerogel thermal insulation composite material layer involved in the present invention is a commercial product, and when used, it is only necessary to stack multiple single layers of aerogel thermal insulation composite material layers according to the required thickness.
[0010] As a preferred solution, in the resin-based composite material layer, the resin matrix includes at least one of a phenolic resin matrix, a bismaleimide resin matrix, a polyimide resin matrix, and a cyanate resin matrix, and the oxide fiber cloth reinforcement phase is composed of oxide fiber cloth. As a more preferred solution, the oxide fiber cloth includes at least one of a two-dimensional quartz fiber cloth and a two-dimensional high-silica fiber cloth. As a more preferred solution, the thickness of the oxide fiber cloth is 0.1 to 1.0 mm. The resin matrix is further preferably a phenolic resin matrix or a bismaleimide resin matrix, because its curing and forming temperature is more suitable for this process.
[0011] As a preferred solution, the fiber felt reinforced ceramic composite material layer, the aerogel thermal insulation composite material layer and the resin-based composite material layer are interconnected by ceramic fiber wires. This connection scheme is mainly based on the fact that the interface bonding strength of the upper and lower surfaces of the aerogel thermal insulation composite material is extremely low when combined with other materials, and it is necessary to connect the layers of materials through high-temperature resistant ceramic fiber wires to form a certain interlayer connection strength without significantly increasing the thermal conductivity of the material. The ceramic fiber wire includes at least one of quartz fiber wire, alumina fiber wire and mullite fiber wire.
[0012] The present invention also provides a method for preparing a multilayer high temperature resistant heat insulating composite material, the method comprising the following steps:
[0013] 1) Designing a mold according to the size requirements of the composite material, wherein the mold includes a female mold and a male mold;
[0014] 2) Filling multiple layers of oxide fiber cloth, oxide fiber felt, multiple layers of aerogel thermal insulation composite material sheets and oxide fiber cloth in order from top to bottom on the male or female mold and closing the corresponding female or male mold to press into the designed shape;
[0015] 3) removing the mold, peeling off the multiple layers of oxide fiber cloth on the oxide fiber felt, retaining the remaining layers, and using oxide fiber threads to pierce and sew the remaining layers into an integral prefabricated part;
[0016] 4) impregnating the peeled off multi-layer oxide fiber cloth with oxide slurry by dipping;
[0017] 5) Brush the resin matrix on the oxide fiber cloth on the lower surface of the integral preform and fully infiltrate it, then fill it back into the positive mold or negative mold;
[0018] 6) After the oxide slurry is brushed on the oxide fiber felt of the integral preform and fully impregnated, a plurality of layers of oxide fiber cloth impregnated with the oxide slurry are laid on the upper surface of the oxide fiber felt, and a negative mold or a positive mold is closed;
[0019] 7) The mold is heated and kept warm to solidify the resin matrix and dry the oxide slurry, the female mold or male mold is removed, and the exposed upper surface of the component is heated and sintered on one side;
[0020] 8) After sintering is completed, completely remove the mold.
[0021] As a preferred solution, the temperature of the single-sided heating sintering is 600-1000° C., and the time is 10-60 minutes.
[0022] As a preferred solution, the oxide slurry is a mixture of nano-oxide aqueous sol and oxide powder. As a more preferred solution, the solid content of the nano-oxide aqueous sol is 5% to 40%, wherein the particle size of the nano-oxide is less than 100nm. As a more preferred solution, the particle size of the oxide powder includes Class A: 200 mesh to 2000 mesh, and Class B: 2000 mesh to 20000 mesh, and the mass ratio of the two is 0.5 to 1.5:1. The mixed use of powders of different particle size grades (including nanoparticles in the sol) is conducive to the formation of better interlayer bonding strength of multi-layer fiber cloth after sintering, and a certain proportion of fine-particle powder is conducive to infiltrating into the gaps between fiber yarns to increase the density of the upper panel composite material (the oxide fiber diameter is about 5 to 10 μm, and powders with a particle size finer than 2000 mesh are more likely to penetrate into the fiber gaps). As a more preferred solution, the mass percentage of the nano-oxide aqueous sol and the oxide powder is 30 to 50%: 50 to 70%. The oxide slurry involved in the present invention comprises at least one of aluminum oxide slurry, mullite slurry, silicon oxide slurry and zirconium oxide slurry. The oxide type in the oxide slurry is preferably consistent with the oxide fiber cloth or fiber felt used. The oxide slurry is obtained by ball milling nano-oxide aqueous sol and oxide powder. The oxide slurry of the present invention is made of nano-oxide aqueous sol and oxide powder according to the above ratio, which can satisfy that the oxide slurry has a large solid content and has good permeability.
[0023] The rapid prototyping method of the multi-layer high temperature resistant heat insulating composite material provided by the present invention specifically comprises the following specific steps:
[0024] Step 1: According to the overall size requirements of the composite component, the thickness of the corresponding upper panel layer (high-density ceramic composite layer), transition layer (fiber felt reinforced ceramic composite layer), middle layer (multi-layer aerogel insulation composite material), and lower panel layer (resin-based composite material) are designed; and a stainless steel mold for pressing the composite component is designed and manufactured. The stainless steel mold includes a female mold and a male mold. The gap size between the male and female molds is the size of the component product design;
[0025] Step 2: Prepare and cut the multi-layer aerogel thermal insulation composite material thin layer flat plate according to the length, width and thickness dimensions designed in step 1, so that its length and width dimensions are sufficient to cover the mold size and have an appropriate margin, so that its total thickness is consistent with the designed middle layer thickness;
[0026] Step 3: Prepare and cut the multi-layer oxide fiber cloth (total thickness is consistent with the designed size) required for the upper panel layer, the oxide fiber felt required for the transition layer, and the single-layer two-dimensional oxide fiber cloth required for the lower panel according to the length, width and thickness designed in Step 1, so that the length and width of each layer are sufficient to cover the mold size and have an appropriate margin;
[0027] Step 4: Lay the materials prepared in steps 2 and 3 on the mold male mold (or female mold) from top to bottom in the order of multi-layer oxide fiber cloth of the upper panel layer, oxide fiber felt of the transition layer, multi-layer aerogel thermal insulation composite material thin layer flat plate, and single-layer two-dimensional oxide fiber cloth of the lower panel, and then close the female mold (or male mold) and press it into place with a screw assembly, so that the layers of materials are tightly attached and the multi-layer aerogel thermal insulation composite material thin layer flat plate is pressed into a designed shape (the shape is controlled by the mold surface);
[0028] Step 5, dismantle the mold, peel off the multiple layers of oxide fiber cloth on the upper panel layer, and keep the remaining layers; and use the oxide fiber thread to pierce and sew the remaining layers of material into a whole using a stainless steel needle;
[0029] Step 6: prepare oxide slurry, place the calculated ratio of oxide sol and oxide powder in a ball mill, and mill at a speed of 200-500 rpm for 30-120 minutes; and put the upper panel layer of multi-layer oxide fiber cloth into the slurry to ultrasonically infiltrate the oxide slurry for standby use;
[0030] Step 7, brush phenolic resin, bismaleimide resin, polyimide or cyanate resin on the oxide fiber cloth of the lower panel of the integral preform obtained in step 5 to make it evenly penetrate, and attach the lower panel to the corresponding surface of the mold;
[0031] Step 8, evenly brush the oxide slurry in step 6 on the transition layer oxide fiber felt on the upper surface; then lay the multi-layer oxide fiber cloth impregnated with the oxide slurry in step 6 layer by layer on the upper surface of the transition layer oxide fiber felt, and after the laying is completed, close the other side of the mold and press it into place with a screw assembly;
[0032] Step 9: Place the mold in an oven for heating and heat preservation to solidify the resin of the lower panel and dry the oxide slurry of the upper panel. After the curing and drying process is completed, remove the upper surface mold.
[0033] Step 10: Use a quartz lamp or a track heater (ceramic heating blanket) to heat the upper surface at a temperature of 600-1000°C for 10-60 minutes;
[0034] Step 11: Remove the mold and machine away the excess parts around the component.
[0035] The preparation method of the multi-layer structure high temperature resistant heat insulating composite material provided by the present invention has the following advantages: 1) The present invention forms a heat insulating core layer by stacking multiple layers of aerogel heat insulating material (aerogel heat insulating felt) flat plates (or coils, which are currently produced on a large scale on the market), and the thickness can be adjusted by the thickness of the single layer and the number of layers, and the thin layer of aerogel composite material can be pressed into the required arc structure without the need for customized mold forming; 2) The upper panel (high temperature resistant surface) of the ceramic composite material in the present invention is formed by one-time pressing of oxide fiber fabric impregnated with oxide slurry with high solid content, and the lower panel (bonding surface) is formed by brushing resin on fiber cloth The matrix is pressed and solidified once, and the overall forming process does not require multiple rounds of long-term repeated sol infiltration processes; 3) The present invention creatively adopts a single-sided heating scheme to enable the upper panel to achieve a ceramic sintering process while ensuring that the resin-based composite material of the lower panel does not undergo a high-temperature sintering process, thereby achieving an excellent combination of the upper panel's high-temperature ablation resistance and the lower panel's bonding performance; 4) A fiber felt reinforced ceramic composite material transition layer is added between the thermal insulation core layer and the high-density upper panel, which, on the one hand, plays a role in adjusting the forming size of the component, and on the other hand, improves the reliability between the upper panel and the thermal insulation layer when subjected to thermal forces.
[0036] Compared with the prior art, the technical solution of the present invention has the following beneficial technical effects:
[0037] The multi-layer high-temperature resistant thermal insulation composite material of the present invention has excellent high-temperature resistance, ablation resistance and bonding performance. More specifically, it has a multi-layer structure: the upper panel is a high-density ceramic composite material layer, which has excellent heat protection, ablation resistance, erosion resistance, load-bearing and other functions; the transition layer is a fiber felt reinforced ceramic composite material layer, which has the functions of adjusting thickness and thermal deformation matching; the middle layer is an aerogel thermal insulation composite material layer, which plays a role of heat insulation and load transfer; and the lower panel is a resin-based composite material layer, which plays a role of high-strength bonding with the metal load-bearing structure.
[0038] The multi-layered high-temperature resistant thermal insulation composite material of the present invention not only plays a role in adjusting the forming size of the component, but also improves the reliability between the upper panel and the thermal insulation layer when subjected to heat and the like, by arranging a fiber felt reinforced ceramic composite material layer between the high-density ceramic composite material layer and the thermal insulation core layer of the aerogel thermal insulation composite material layer.
[0039] During the preparation process of the multi-layer high-temperature resistant heat-insulating composite material of the present invention, a single-sided heating method is adopted so that the upper panel layer can realize the ceramic sintering process while ensuring that the lower panel resin-based composite material is not affected by the high-temperature process, thereby achieving an excellent combination of the upper panel's anti-high-temperature ablation performance and the lower panel's bonding performance.
[0040] The preparation method of the multi-layer high temperature resistant heat insulating composite material of the present invention can realize one-time rapid overall forming, has the advantages of simple manufacturing process, short cycle, low cost, etc., and meets the requirements of large-scale batch production. BRIEF DESCRIPTION OF THE DRAWINGS
[0041] Figure 1 It is a schematic diagram of the structure of a multi-layer high temperature resistant heat insulation composite material.
[0042] Figure 2 It is a schematic diagram of the mold pressing and forming state of the multi-layer high-temperature resistant and heat-insulating composite material.
[0043] Figure 3 The actual curved component after forming (a) and the enlarged side view (b).
[0044] Figure 4 The debonding interface conditions of three types of samples: aluminum alloy bonded to quartz composite panel (left), phenolic resin composite panel (middle) and aluminum alloy (right) after tensile shear testing.
[0045] Among them, 1 is a high-density ceramic composite upper panel layer, 2 is a fiber felt reinforced ceramic composite transition layer, 3 is a multi-layer aerogel thermal insulation composite middle layer, 4 is a ceramic fiber wire used for connecting multi-layer materials, 5 is a resin-based composite lower panel layer, 6 is a stainless steel positive mold used for pressing and forming, and 7 is a stainless steel negative mold used for pressing and forming. DETAILED DESCRIPTION
[0046] The present invention is further described in detail below with reference to the embodiments, but the protection scope of the claims of the present invention is not limited by the specific embodiments.
[0047] Example 1
[0048] Design and manufacture a multi-layer high temperature resistant heat insulation composite material arc-shaped structural member, the shape of the arc-shaped structure is as follows Figure 2 The material structure in the mold gap is shown in FIG. 1 . The overall thickness of the arc part is 12 mm, of which the upper panel layer of the high-density ceramic composite material is 1.2 mm thick, the transition layer of the fiber felt reinforced ceramic composite material is about 0.3 mm thick, the middle layer of the multilayer aerogel insulation composite material is 10 mm thick, and the lower panel layer of the resin-based composite material is 0.5 mm thick.
[0049] Step 1: According to the overall size requirements of the composite component, the corresponding high-density ceramic composite upper panel layer, fiber felt reinforced ceramic composite transition layer, multi-layer aerogel insulation composite middle layer, and resin-based composite lower panel layer are designed. The thickness of each layer is as follows: the upper panel layer is pressed with 6 layers of 0.2mm quartz fiber plain cloth, and the transition layer is made of a surface density of about 60g / m 2Quartz fiber needle felt (the density is about 0.2g / cm when pressed to 0.3mm thickness) 3 ), the middle layer of the thermal insulation material uses 5 layers of 2mm thick silica aerogel composite material, and the lower panel uses a single layer of 0.5mm thick quartz fiber twill cloth. Design and manufacture stainless steel molds for pressing composite components such as Figure 2 shown.
[0050] Step 2: Prepare and cut 5 layers of aerogel thermal insulation composite material thin-layer flat plates according to the length, width and thickness designed in step 1, so that the length and width are sufficient to cover the mold size and have an appropriate margin (about 1-2 cm more than the edge of the mold);
[0051] Step 3: Prepare and cut the 6 layers of quartz fiber cloth required for the upper panel layer, the needle-punched fiber felt required for the transition layer, and the single layer of twill quartz fiber cloth required for the lower panel according to the length, width and thickness designed in step 1, so that the length and width of each layer are sufficient to cover the mold size and have an appropriate margin (about 1~2cm more than the edge of the mold);
[0052] Step 4: pre-pressing, laying the materials prepared in steps 2 and 3 on the positive mold from top to bottom in the order of 6 layers of quartz fiber cloth on the upper panel layer, needle-punched fiber felt on the transition layer, 5 layers of aerogel thermal insulation composite material thin flat plate, and single layer of twill fiber cloth on the lower panel, and then closing the negative mold and pressing it into place with a screw assembly, so that the layers of materials are close together and the 5 layers of aerogel thermal insulation composite material thin flat plate are pressed into the designed shape (the shape is controlled by the mold surface);
[0053] Step 5: Remove the mold, peel off the 6 layers of quartz fiber cloth on the upper panel layer, and keep the remaining layers; and use a twisted quartz fiber line of about 400TEX to sew the remaining layers of material into a whole with a stainless steel needle, with a suturing density of about 10×10mm;
[0054] Step 6: Prepare silicon oxide slurry, place nano silica sol (solid content 20%), quartz powder A (about 600 mesh), and quartz powder B (about 10000 mesh) in a ball mill at a weight ratio of 4:3:3, and ball mill for 60 minutes at a speed of 300 rpm; and put the 6 layers of quartz fiber cloth used for the upper panel layer into the ball-milled slurry and ultrasonically infiltrate the silicon oxide slurry for use;
[0055] Step 7, brush phenolic resin on the lower panel fiber cloth of the integral prefabricated component obtained in step 5 to make it evenly permeated, and fit the lower panel to the surface of the male mold;
[0056] Step 8, evenly brush the silicon oxide slurry in step 6 on the transition layer needle-punched fiber felt on the upper surface; then lay the 6 layers of quartz fiber cloth impregnated with silicon oxide slurry in step 6 layer by layer on the upper surface of the transition layer needle-punched fiber felt, and after the laying is completed, close the female mold and press it into place with a screw assembly;
[0057] Step 9: Place the mold in an oven for heating and heat preservation to solidify the resin of the lower panel and dry the silicon oxide slurry of the upper panel. After the curing and drying process is completed, remove the upper surface mold.
[0058] Step 10: Use a crawler heater (ceramic heating blanket) to heat the upper surface at a temperature of 700°C for 20 minutes;
[0059] Step 11: Remove the mold and machine away the excess parts around the component.
[0060] Simultaneously with Example 1, a 300 mm×300 mm flat plate sample (thickness 12 mm, thickness of each layer and the like are consistent with those in Example 1) was manufactured as a density and thermal conductivity test piece I.
[0061] Formed arc parts such as Figure 3 As shown in Figure a. The upper and lower panels of the arc-shaped part have no wrinkles, cracks, pits or other defects. After testing, the arc-shaped surface dimensions basically meet the design value ±0.2mm. The side of the arc-shaped part is enlarged as shown in Figure a. Figure 3 As shown in Figure b, the multi-layer structures are connected by fibers and fit tightly after being pressed by a mold without defects such as delamination and cracking.
[0062] Example 2
[0063] A multi-layer high-temperature resistant thermal insulation composite arc-shaped structural component is designed and manufactured. The overall thickness of the arc-shaped component is 18 mm, of which the upper panel layer of the high-density ceramic composite material is 2 mm thick, the transition layer of the fiber felt reinforced ceramic composite material is about 0.5 mm thick, the middle layer of the multi-layer aerogel thermal insulation composite material is 15 mm thick, and the lower panel layer of the resin-based composite material is 0.5 mm thick.
[0064] Step 1: According to the overall size requirements of the composite component, the corresponding high-density ceramic composite upper panel layer, fiber felt reinforced ceramic composite transition layer, multi-layer aerogel insulation composite middle layer, and resin-based composite lower panel layer are designed. The thickness of each layer is as follows: the upper panel layer is pressed with 10 layers of 0.2mm alumina fiber plain cloth, the transition layer is made of a surface density of about 150g / m 2 Alumina fiber needle felt (the density is about 0.3g / cm when pressed to 0.5mm thickness) 3), the middle layer of the heat insulation material uses 5 layers of 3mm thick silica aerogel composite material (the same model as in Example 1), and the lower panel uses a single layer of 0.5mm thick quartz fiber twill cloth; design and manufacture a stainless steel mold for pressing composite material components such as Figure 2 shown.
[0065] Step 2: Prepare and cut 5 layers of aerogel thermal insulation composite material thin-layer flat plates according to the length, width and thickness designed in step 1, so that the length and width are sufficient to cover the mold size and have an appropriate margin (about 1-2 cm more than the edge of the mold);
[0066] Step 3: Prepare and cut 10 layers of alumina fiber cloth required for the upper panel layer, needle-punched fiber felt required for the transition layer, and a single layer of twill quartz fiber cloth required for the lower panel according to the length, width, and thickness designed in step 1, so that the length and width of each layer are sufficient to cover the mold size and have an appropriate margin (about 1-2 cm more than the edge of the mold);
[0067] Step 4: pre-pressing, laying the materials prepared in steps 2 and 3 on the positive mold from top to bottom in the order of 6 layers of alumina fiber cloth on the upper panel layer, needle-punched fiber felt on the transition layer, 5 layers of aerogel thermal insulation composite material thin flat plate, and single layer of twill fiber cloth on the lower panel, and then closing the negative mold and pressing it into place with a screw assembly, so that the layers of materials are tightly attached and the 5 layers of aerogel thermal insulation composite material thin flat plate are pressed into the designed shape (the shape is controlled by the mold surface);
[0068] Step 5: Remove the mold, peel off 10 layers of alumina fiber cloth on the upper panel layer, and keep the remaining layers; and use about 600 TEX twisted alumina fiber thread to sew the remaining layers of material into a whole with a stainless steel needle, with a suturing density of about 10×10mm;
[0069] Step 6: Prepare alumina slurry. Place nano alumina sol (solid content 25%), alumina powder A (about 1000 mesh), and alumina powder B (about 10000 mesh) in a ball mill at a weight ratio of 5:3:2, and mill at a speed of 300 rpm for 60 minutes; and put 10 layers of alumina fiber cloth used for the upper panel layer into the ball-milled slurry and ultrasonically infiltrate the alumina slurry for use;
[0070] Step 7: Brush the bismaleimide resin on the lower panel fiber cloth of the integral prefabricated part obtained in step 5 to make it evenly penetrate, and fit the lower panel to the surface of the male mold;
[0071] Step 8, evenly brush the alumina slurry in step 6 on the transition layer needle-punched fiber felt on the upper surface; then lay the 10 layers of alumina fiber cloth impregnated with alumina slurry in step 6 layer by layer on the upper surface of the transition layer needle-punched fiber felt, and after the laying is completed, close the female mold and press it into place with a screw assembly;
[0072] Step 9: Place the mold in an oven for heating and heat preservation to solidify the resin of the lower panel and dry the alumina slurry of the upper panel. After the curing and drying process is completed, remove the upper surface mold.
[0073] Step 10: Use a crawler heater (ceramic heating blanket) to heat the upper surface at a temperature of 1000°C for 30 minutes;
[0074] Step 11: Remove the mold and machine away the excess parts around the component.
[0075] Simultaneously with Example 2, a 300 mm×300 mm flat plate sample (thickness 18 mm, thickness of each layer and the like are consistent with those in Example 2) was manufactured as the density and thermal conductivity test specimen II.
[0076] Comparative Example 1
[0077] This comparative example adopts the traditional sol-gel method for the densification composite process of the panel fiber. The material structure is affected by the process and is mainly different from Example 1 in the following two aspects: on the one hand, referring to the prior art such as CN102642350A, the sol-gel method overall impregnation process makes the upper panel and the lower panel simultaneously impregnate and composite the same silicon oxide matrix, and the lower panel cannot be made into a resin-based composite material; on the other hand, the sol-gel method cannot form sufficient interlayer strength between the 6 layers of quartz fiber cloth on the upper panel and the fiber cloth and the transition layer material, so the upper panel fiber cloth must be sewn with the overall structure (step 5); other structural aspects are basically the same as Example 1.
[0078] Design and manufacture a multi-layer high temperature resistant heat insulation composite material arc-shaped structural member, the shape of the arc-shaped structure is as follows Figure 2 The material structure in the mold gap is shown in FIG. 1 . The overall thickness of the arc part is 12 mm, of which the upper panel layer of the high-density ceramic composite material is 1.2 mm thick, the transition layer of the fiber felt reinforced ceramic composite material is about 0.3 mm thick, the middle layer of the multi-layer aerogel insulation composite material is 10 mm thick, and the lower panel layer of the ceramic composite material is 0.5 mm thick.
[0079] Steps 1 to 4 are consistent with those in Example 1, and are as follows:
[0080] Step 1: According to the overall size requirements of the composite component, the corresponding high-density ceramic composite upper panel layer, fiber felt reinforced ceramic composite transition layer, multi-layer aerogel insulation composite middle layer, and ceramic matrix composite lower panel layer are designed. The thickness of each layer is as follows: the upper panel layer is pressed with 6 layers of 0.2mm quartz fiber plain cloth, and the transition layer is made of a surface density of about 60g / m 2 Quartz fiber needle felt (the density is about 0.2g / cm when pressed to 0.3mm thickness) 3), the middle layer of the heat insulation material uses 5 layers of 2mm thick silica aerogel composite material, and the lower panel uses a single layer of 0.5mm thick quartz fiber twill cloth. The stainless steel mold used to press the composite material component is shown in 2.
[0081] Step 2: Prepare and cut 5 layers of aerogel thermal insulation composite material thin-layer flat plates according to the length, width and thickness designed in step 1, so that the length and width are sufficient to cover the mold size and have an appropriate margin (about 1-2 cm more than the edge of the mold);
[0082] Step 3: Prepare and cut the 6 layers of quartz fiber cloth required for the upper panel layer, the needle-punched fiber felt required for the transition layer, and the single layer of twill quartz fiber cloth required for the lower panel according to the length, width and thickness designed in step 1, so that the length and width of each layer are sufficient to cover the mold size and have an appropriate margin (about 1~2cm more than the edge of the mold);
[0083] Step 4: pre-pressing, laying the materials prepared in steps 2 and 3 on the positive mold from top to bottom in the order of 6 layers of quartz fiber cloth on the upper panel layer, needle-punched fiber felt on the transition layer, 5 layers of aerogel thermal insulation composite material thin flat plate, and single layer of twill fiber cloth on the lower panel, and then closing the negative mold and pressing it into place with a screw assembly, so that the layers of materials are close together and the 5 layers of aerogel thermal insulation composite material thin flat plate are pressed into the designed shape (the shape is controlled by the mold surface);
[0084] Step 5: Remove the mold and use a twisted quartz fiber thread of about 400 TEX to sew all the layers of materials into a whole using a stainless steel needle with puncture, and the suturing density is about 10×10mm;
[0085] Step 6: clamp the sewn components in a stainless steel mold, tighten them, and then use the sol-gel method to make the panel fibers absorb silica sol in a vacuum container, and then gel them in an oven at 80°C, and repeat the dipping and gelling for 10 times;
[0086] Step 7: Remove the mold and place the entire component in a high-temperature furnace for heat treatment at 700°C for 20 minutes.
[0087] Step 8: Remove the mold and machine away the excess parts around the component.
[0088] Simultaneously with Comparative Example 1, a 300 mm×300 mm flat plate sample (thickness 12 mm, thickness of each layer and the like are consistent with those in Comparative Example 1) was manufactured as the density and thermal conductivity test specimen III.
[0089] Performance Test:
[0090] Density and thermal conductivity tests:
[0091] The density and thermal conductivity of test piece I, comparative sample I (the same aerogel insulation material as in Examples 1 and 2, single layer thickness 2 mm, 6 layers stacked, total thickness 12 mm), test piece II, comparative sample II (the same aerogel insulation material as in Examples 1 and 2, single layer thickness 3 mm, 6 layers stacked, total thickness 18 mm) and test piece III were tested respectively, and the test results are shown in Table 1. The thermal conductivity of test pieces I and II is about 10% higher than that of pure aerogel insulation material (comparative samples I and II). Considering that the panel layer accounts for a certain thickness ratio, its thermal conductivity is much greater than that of aerogel insulation material (more than one order of magnitude difference), indicating that after the integral forming process, the core layer of the aerogel insulation material basically retains the original thermal insulation performance; the density of test piece III is about 10% higher than that of test piece I, and the thermal conductivity is nearly 30% higher, indicating that the scheme of the present invention can better retain the thermal insulation performance of aerogel insulation material than the sol-gel integral impregnation process.
[0092]
[0093] Bond strength test:
[0094] The interface strength test was conducted by bonding samples with the same adhesive (silicone rubber). The test sample scheme for bonding is as follows:
[0095] Solution 1: Aluminum alloy sticks to aluminum alloy;
[0096] Solution 2: Quartz fiber reinforced phenolic resin composite material (material selection and forming process are the same as those in Example 1) bonded with aluminum alloy;
[0097] Solution 3: quartz / quartz composite material (quartz fiber fabric is impregnated with silica sol 10 times by the same sol-gel process as in Comparative Example 1 and then sintered at 700° C.) bonded with aluminum alloy;
[0098] The bond interface strengths were tested as shown in Table 2. The interface debonding after the test is shown in Table 2. Figure 4 As shown, Scheme 1 ( Figure 4 Sample on the right) and Solution 2 ( Figure 4 The samples in the middle of the adhesive layer are all sheared and debonded from the middle of the adhesive layer (the failure mode is consistent). Scheme 3 ( Figure 4 The form of debonding failure at the interface of the bonded sample (sample on the left) is basically that the thin layer on the surface of the ceramic composite material is stuck and falls off by the adhesive layer.
[0099]
Claims
1. A multi-layer high temperature resistant heat insulation composite material, characterized in that: From top to bottom, it includes a high-density ceramic composite material layer, a fiber felt reinforced ceramic composite material layer, an aerogel thermal insulation composite material layer and a resin-based composite material layer; wherein the high-density ceramic composite material layer is composed of a composite of an oxide fiber cloth reinforcement phase and an oxide ceramic phase, the fiber felt reinforced ceramic composite material layer is composed of a composite of an oxide fiber felt reinforcement phase and an oxide ceramic phase, the aerogel thermal insulation composite material layer is composed of a composite of an oxide fiber felt reinforcement phase and an oxide aerogel, and the resin-based composite material layer is composed of a composite of an oxide fiber cloth reinforcement phase and a resin matrix; In the fiber felt reinforced ceramic composite material layer, the oxide ceramic phase includes at least one of aluminum oxide, mullite, silicon oxide or zirconium oxide, and the oxide fiber felt reinforcement phase is composed of oxide fiber felt; The density of the oxide fiber felt is 0.1-0.5 g / cm 3 ; The oxide fiber felt includes at least one of quartz fiber felt, alumina fiber felt, mullite fiber felt, and zirconia fiber felt; In the resin-based composite material layer, the resin matrix includes at least one of a phenolic resin matrix, a bismaleimide resin matrix, and a cyanate resin matrix, and the oxide fiber cloth reinforcement phase is composed of oxide fiber cloth; The oxide fiber cloth includes at least one of a two-dimensional quartz fiber cloth and a two-dimensional high silica fiber cloth; The thickness of the oxide fiber cloth is 0.1-1.0 mm; The fiber felt reinforced ceramic composite material layer, the aerogel thermal insulation composite material layer and the resin-based composite material layer are interconnected by ceramic fiber wires; the ceramic fiber wires include at least one of quartz fiber wires, alumina fiber wires and mullite fiber wires.
2. The multi-layer high temperature resistant heat insulating composite material according to claim 1, characterized in that: In the high-density ceramic composite material layer, the oxide ceramic phase includes at least one of aluminum oxide, mullite, silicon oxide or zirconium oxide, and the oxide fiber cloth reinforcement phase is composed of multiple layers of oxide fiber cloth, each layer of oxide fiber cloth is 0.1-0.5 mm thick, and the total thickness is 0.5-10 mm.
3. The multi-layer high temperature resistant heat insulating composite material according to claim 2, characterized in that: The oxide fiber cloth includes at least one of quartz fiber cloth, alumina fiber cloth, mullite fiber cloth and zirconium oxide fiber cloth.
4. The multi-layer high temperature resistant heat insulating composite material according to claim 1, characterized in that: In the aerogel heat-insulating composite material layer, the aerogel includes at least one of silica aerogel, alumina aerogel, silica-alumina binary aerogel, and mullite aerogel, and the oxide fiber felt reinforcement phase is composed of high-temperature resistant fibers; The high temperature resistant fiber includes at least one of quartz fiber, alumina fiber, basalt short fiber and mullite fiber.
5. The multi-layer high temperature resistant heat insulating composite material according to claim 1 or 4, characterized in that: The aerogel thermal insulation composite material layer is composed of a plurality of single-layer aerogel thermal insulation composite material layers, with a total thickness ranging from 3 to 50 mm, and a thickness of each single layer ranging from 0.3 to 3 mm.
6. A method for preparing a multilayer high temperature resistant heat insulating composite material according to claim 1, 2, 3 or 4, characterized in that: The following steps are involved: 1) Designing a mold according to the size requirements of the composite material, wherein the mold includes a female mold and a male mold; 2) Filling multiple layers of oxide fiber cloth, oxide fiber felt, multiple layers of aerogel thermal insulation composite material sheets and oxide fiber cloth in order from top to bottom on the male or female mold and closing the corresponding female or male mold to press into the designed shape; 3) removing the mold, peeling off the multiple layers of oxide fiber cloth on the oxide fiber felt, retaining the remaining layers, and using oxide fiber threads to pierce and sew the remaining layers into an integral prefabricated part; 4) impregnating the peeled off multi-layer oxide fiber cloth with oxide slurry by dipping; 5) Brush the resin matrix on the oxide fiber cloth on the lower surface of the integral preform and fully infiltrate it, then fill it back into the positive mold or negative mold; 6) After the oxide slurry is brushed on the oxide fiber felt of the integral preform and fully impregnated, a plurality of layers of oxide fiber cloth impregnated with the oxide slurry are laid on the upper surface of the oxide fiber felt, and a negative mold or a positive mold is closed; 7) The mold is heated and kept warm to solidify the resin matrix and dry the oxide slurry, the female mold or male mold is removed, and the exposed upper surface of the component is heated and sintered on one side; 8) After sintering is completed, completely remove the mold.
7. The method for preparing a multi-layer high temperature resistant heat insulating composite material according to claim 6, characterized in that: The single-sided heating sintering temperature is 600-1000°C and the time is 10-60 minutes; The oxide slurry is a mixture of nano-oxide aqueous sol and oxide powder; The solid content of the nano-oxide aqueous sol is 5% to 40%, wherein the particle size of the nano-oxide is less than 100 nm; The particle sizes of the oxide powders include Class A: 200-2000 mesh, and Class B: 2000-20000 mesh, and the mass ratio of the two is 0.5-1.5:1; The mass percentage composition of the nano-oxide aqueous sol and the oxide powder is 30-50%:50-70%.
Citation Information
Patent Citations
Ceramic composite material of high temperature insulation sandwich structure and method for preparing ceramic composite material
CN102642350A
Sandwich structure thermal protection material with high panel strength and making method thereof
CN108116002A
Low-cost and high-temperature-resistant ceramic composite material and rapid preparation method thereof
CN109824372A
Aerogel heat-proof material with high-efficiency heat-insulation sandwich structure and preparation method thereof
CN111703142A
Multilayer structure composite high-temperature-resistant thermal protection material and preparation method thereof
CN111592369A
Cited By
High-temperature heat-insulation noise-reduction far-infrared multifunctional composite woven body and preparation method thereof
CN120443401A